PEMA / ENR-50 blend based polymer electrolytes : some electrical properties / Nursyazwani Mohamad Sukri - Mohamad Sukri, Nursyazwani (2016)
In this work, PEMA was used as the principle host to prepare PEMA/ENR-50 blend, PEMA/ENR-50-LiCF3SO3 and PEMA/ENR-50-LiCF3SO3-EMIMTFSI systems using solution casting technique. The samples were characterized using Electrical Impedance Spectroscopy (EIS), X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Differential Scanning Calorimetry (DSC) in order to investigate their electrical, structural and thermal properties. The polymer blend with PEMA/ENR-50 of ratio 70:30 yielded the most amorphous film. This blend system was selected for the preparation of polymer electrolytes with LiCF3S03 as a dopant salt. Impedance study showed that the conductivity of the blend based electrolyte system increases with increasing LiCF3S03 concentration. The system containing 40wt.% of LiCF3S03 salt exhibited optimum room temperature conductivity of 3.64>.